Climate‐driven spatial mismatches between British orchards and their pollinators: increased risks of pollination deficits. (2nd May 2014) - Polce, Chiara; Garratt, Michael P; Termansen, Mette; Ramirez‐Villegas, Julian; Challinor, Andrew J; Lappage, Martin G; Boatman, Nigel D; Crowe, Andrew; Endalew, Ayenew Melese; Potts, Simon G; Somerwill, Kate E; Biesmeijer, Jacobus C
Abstract Understanding how climate change can affect crop‐pollinator systems helps predict potential geographical mismatches between a crop and its pollinators, and therefore identify areas vulnerable to loss of pollination services. We examined the distribution of orchard species (apples, pears, plums and other top fruits) and their pollinators in Great Britain, for present and future climatic conditions projected for 2050 under the SRES A1B Emissions Scenario. We used a relative index of pollinator availability as a proxy for pollination service. At present, there is a large spatial overlap between orchards and their pollinators, but predictions for 2050 revealed that the most suitable areas for orchards corresponded to low pollinator availability. However, we found that pollinator availability may persist in areas currently used for fruit production, which are predicted to provide suboptimal environmental suitability for orchard species in the future. Our results may be used to identify mitigation options to safeguard orchard production against the risk of pollination failure in Great Britain over the next 50 years; for instance, choosing fruit tree varieties that are adapted to future climatic conditions, or boosting wild pollinators through improving landscape resources. Our approach can be readily applied to other regions and crop systems, and expanded to include different climatic scenarios.